The phylogenetic significance of leaf anatomical traits of southern African Oxalis - Jooste, Michelle; Dreyer, Léanne L; Oberlander, Kenneth C (BMC evolutionary biology, 2016)
BACKGROUND: The southern African Oxalis radiation is extremely morphologically variable. Despite recent progress in the phylogenetics of the genus, there are few morphological synapomorphies supporting DNA-based clades. Leaflet anatomy can provide an understudied and potentially valuable source of information on the evolutionary history and systematics of this lineage. Fifty-nine leaflet anatomical traits of 109 southern African Oxalis species were assessed in search of phylogenetically significant characters that delineate clades. RESULTS: A combination of 6 leaflet anatomical traits (stomatal position, adaxial epidermal cells, abaxial epidermal cells, mesophyll, sheath around vascular tissue, degree of leaflet conduplication) clearly support various clades defined by previous DNA-based phylogenetic work. Other, mostly continuous leaflet anatomical traits were highly variable and showed less phylogenetic pattern. CONCLUSIONS: Major and unexpected findings include the transition from ancestral hypostomatic leaflets to adaxially-located stomata in the vast majority of southern African Oxalis, the loss of semi-swollen AB epidermal cells and the gain of swollen adaxial and abaxial epidermal cells in selected clades, and multiple changes from ancestral bifacial mesophyll to isobilateral or homogenous mesophyll types. The information gathered in this study will aid in the taxonomic revision of this speciose member of the Greater Cape Floristic Region and provide a basis for future hypotheses regarding its radiation.
Keywords: cévní svazky rostlin; Phenotype; biologická evoluce; Mesophyll Cells; Quantitative Trait, Heritable; listy rostlin; průduchy rostlin; Plant Leaves; kvantitativní znak dědičný; Oxalidaceae; mezofylové buňky; Phylogeny; duplikace genu; Plant Stomata; fenotyp; trichomy; Biological Evolution; fylogeneze; Gene Duplication; Trichomes; Plant Vascular Bundle